Paper on Searching and Indexing Using Elasticsearch (International Journal of Engineering and Computer Science, 2017)
In today’s era, it is inconceivable to use traditional techniques / RDBMS to analyse the data as it is growing very quickly. Big data offers the solution for analysing large amount of data. Using technique of Elasticsearch, access to data can be made faster. Elasticsearch is a search engine based on Lucene. It is near real time search platform. Elasticsearch uses the concept of indexing to make the search faster. This paper elaborates the search technique of Elasticsearch.